Phosphate-modified graphite phase carbon nitride loaded cobalt hydroxide composite photo-fenton catalytic material, and preparation method and application thereof
The graphitic carbon nitride-supported cobalt hydroxide composite material modified with phosphate ions achieved effective separation of photogenerated carriers and optimization of surface active sites, solving the problem of low photocatalytic efficiency of g-C3N4-based photo-Fenton materials and realizing efficient degradation of antibiotic pollutants.
Patent Information
- Application Number
- CN202611258715.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-11-06
Smart Images

Figure CN123038852A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional nanomaterials and environmental protection technology, specifically relating to a phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material, its preparation method, and its application. Background Technology
[0002] In recent years, the extensive use of antibiotics in medical, livestock, and aquaculture fields has led to increasingly prominent problems of antibiotic residues in natural water bodies. Antibiotics that persist in the aquatic environment for extended periods can easily induce the generation and spread of resistance genes, posing a serious threat to the balance of aquatic ecosystems and human health. Therefore, developing efficient, economical, and environmentally friendly water treatment technologies to achieve the deep removal of antibiotic pollutants has become a research hotspot in the field of environmental science.
[0003] Semiconductor photocatalytic Fenton oxidation technology based on persulfate (PMS) is widely recognized as one of the most promising technologies for advanced wastewater treatment due to its advantages such as mild reaction conditions, wide pH adaptability, high oxidation efficiency, and environmental friendliness. The basic principle of this technology is that a transition metal catalyst supported on the semiconductor surface reacts with PMS in solution, activating and generating sulfate radicals (SO4•-). - The catalyst contains highly reactive oxidizing species such as hydroxyl radicals (•OH), which oxidize and degrade organic pollutants in the water. At the same time, the semiconductor carrier generates photogenerated electrons under light excitation. These electrons migrate to the material surface and reduce high-valence metal ions to low-valence states, thus achieving the cyclic regeneration of the active sites of the Fenton reaction and maintaining the long-term stability of the catalyst.
[0004] Graphitic carbon nitride (g-C3N4), as a non-metallic polymer semiconductor material, is considered an ideal photocatalytic support material due to its suitable band structure, excellent chemical and thermal stability, and abundant raw material sources. However, unmodified bulk g-C3N4 suffers from inherent defects such as high recombination rate of photogenerated carriers and a limited number of surface active sites, which severely restricts further improvement of its photocatalytic efficiency. Existing research shows that preparing ultrathin g-C3N4 nanosheets can effectively shorten the migration distance of photogenerated carriers from the bulk phase to the surface and inhibit carrier recombination in the bulk phase. At the same time, introducing polar functional groups into the g-C3N4 surface can improve its surface hydrophilicity and dispersibility, and enhance its adsorption and activation ability for PMS and pollutants, thereby synergistically improving the performance of photo-Fenton reaction. Nevertheless, there are currently insufficient research reports on combining ultrathin nanosheet structure design with surface functional group modification to construct efficient g-C3N4-based photo-Fenton water purification materials. Furthermore, systematic research on the synergistic effect of the two strategies on the activation mechanism and catalytic performance of PMS is still lacking, and further exploration and development are urgently needed. Summary of the Invention
[0005] This invention addresses the key technical problems of severe photogenerated carrier recombination and insufficient surface active sites in existing g-C3N4-based photo-Fenton materials by proposing a phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material. This invention utilizes a nitrogen-rich phosphate precursor-assisted thermal polymerization method to prepare phosphate-modified g-C3N4 ultrathin nanosheet photocatalytic materials, followed by in-situ loading of Co(OH)2 nanoparticles onto their surface. This achieves both effective separation of photogenerated electrons and holes and promotes the photo-Fenton water purification activity of the catalyst surface. In this material system, the ultrathin structure effectively shortens the migration distance of photogenerated carriers, thus achieving effective separation of photogenerated electrons and holes; surface phosphate modification effectively promotes the in-situ generation of Co(OH)2 nanoparticles and the transport of photogenerated electrons and activation of PMS, thereby promoting the generation of oxygen-containing active species. The synergistic effect of these two structural features maximizes the photo-Fenton capability of the synthesized material.
[0006] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows: A phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material, the preparation method of which includes the following steps:
[0007] (1) Mix the nitrogen-rich precursor and the phosphorylated nitrogen-rich precursor evenly, and calcine the resulting mixture in an air atmosphere to obtain phosphate-modified graphitic carbon nitride.
[0008] (2) The phosphate-modified graphitic carbon nitride obtained in step (1) was added to the cobalt nitrate (Co(NO3)2) ethanol solution, stirred evenly, and then sodium hydroxide (NaOH) solution was added dropwise; the mixture was stirred at 10 ℃ - 60 ℃ for 1 h - 10 h, taken out, washed with deionized water and ethanol, and dried to obtain the phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalyst.
[0009] Furthermore, the nitrogen-rich precursor is selected from one or a mixture of two or more of cyanamide, dinitrile diamine, urea, or melamine.
[0010] Furthermore, the phosphorylated nitrogen-rich precursor is selected from one or a mixture of two or more of cyanamide phosphate, diamine dinitrile phosphate, urea phosphate, or melamine phosphate.
[0011] Further, in step (1), the mass ratio of nitrogen-rich precursor to phosphorylated nitrogen-rich precursor is 10: (0.1 - 2). Preferably, the mass ratio of nitrogen-rich precursor to phosphorylated nitrogen-rich precursor is 10: (0.5 - 1).
[0012] Further, in step (1), the calcination conditions are: holding at 400 ℃ - 600 ℃ for 1 h - 6 h. Preferably, the calcination conditions are: holding at 500 ℃ - 550 ℃ for 1 h - 3 h.
[0013] Further, in step (2), the mass ratio of phosphate-modified graphitic carbon nitride to cobalt nitrate is 100:(1-10).
[0014] Further, in step (2), the molar ratio of cobalt nitrate to sodium hydroxide is 1:(1-10).
[0015] The present invention relates to the application of phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material in the photo-Fenton purification of antibiotics in water.
[0016] Further, the method is as follows: phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalyst is added to water containing antibiotics. After dark reaction adsorption equilibrium is reached, persulfate (PMS) is added to the solution, and photo-Fenton purification reaction is carried out under visible light.
[0017] Furthermore, the antibiotics include ciprofloxacin, ofloxacin, norfloxacin, and tetracycline.
[0018] The beneficial effects of this invention are:
[0019] 1. This invention uses a nitrogen-rich organic phosphate-assisted thermal polymerization method to synthesize phosphate-modified ultrathin g-C3N4 nanosheets in situ. The method is simple to operate and can efficiently achieve large-scale and reproducible preparation of the target material, showing good potential for large-scale production.
[0020] 2. This invention, through the synergistic design of ultrathin nanosheet structure and surface phosphate modification, effectively promotes the separation and migration of photogenerated carriers, while optimizing the distribution of surface active sites and electron transport paths. This deeply integrates the photocatalytic process with the Fenton oxidation reaction, significantly improving the overall water purification efficiency. It provides valuable technical reference and insights for the functional design of novel photo-Fenton catalytic materials.
[0021] 3. The process of this invention is simple, easy to operate, and has low energy consumption, making it suitable for mass production.
[0022] 4. The material synthesized in this invention has high photo-Fenton activity, good stability and practicality, and has important practical application prospects in the fields of advanced drinking water treatment and wastewater purification.
[0023] 5. This invention maximizes the synergistic effect of photocatalysis and Fenton oxidation by combining two strategies: "accelerating carrier separation with ultrathin structure" and "phosphate-mediated electron transport and surface active site optimization". This significantly improves the purification and disinfection efficiency of the material for antibiotic pollutants in water under simulated sunlight, and provides a new technical path for the design of high-efficiency photo-Fenton water purification materials. Attached Figure Description
[0024] Figure 1 XRD patterns representing the crystal structures of UCN, PCN, and Co(OH)2@PCN prepared in Example 1.
[0025] Figure 2 SEM images of UCN (a), PCN (b) and Co(OH)2@PCN (c) prepared in Example 1.
[0026] Figure 3 The light absorption curves of UCN, PCN and Co(OH)2@PCN prepared in Example 1 are shown.
[0027] Figure 4 Instantaneous photocurrent chromatograms of UCN, PCN and Co(OH)2@PCN prepared in Example 1.
[0028] Figure 5 TEM (a) and partial magnified view (b) of the Co(OH)2@PCN material prepared in Example 1.
[0029] Figure 6 TEM images of PMCN (a) and Co(OH)2@PMCN (b) prepared in Example 2.
[0030] Figure 7 The image shows the results of photo-Fenton degradation of ciprofloxacin by UCN, PCN, Co(OH)2@UCN and Co(OH)2@PCN under visible light irradiation.
[0031] Figure 8 The image shows the results of photo-Fenton degradation of various antibiotic pollutants by Co(OH)2@PCN prepared in Example 1 under visible light irradiation. Detailed Implementation
[0032] The design concept of this invention is as follows:
[0033] First, this invention employs a nitrogen-rich organic phosphate-assisted thermal polymerization method to synthesize phosphate-modified ultrathin graphitic carbon nitride (g-C3N4) nanosheets (PCN) in situ. This ultrathin structure, approximately 5 nm thick, significantly shortens the diffusion distance of photogenerated carriers migrating from the bulk phase to the surface, effectively suppressing bulk carrier recombination. This substantially improves the separation efficiency of photogenerated electrons and holes, fundamentally solving the inherent bottleneck of low photocatalytic efficiency in traditional bulk g-C3N4.
[0034] Secondly, the phosphate groups introduced in situ onto the surface of ultrathin graphitic carbon nitride nanosheets (PCN) serve two main purposes. First, they act as anchoring sites, inducing highly dispersed and uniformly loaded Co(OH)₂ nanoparticles on the PCN surface through coordination, thus avoiding the loss of active sites caused by metal particle agglomeration. Second, phosphate groups possess strong electron-withdrawing properties, acting as electron transport bridges to promote the rapid migration of photogenerated electrons from the g-C₃N₄ framework to the surface-loaded Co(OH)₂ active sites, thereby effectively reducing Co. 3+ For Co 2+ This accelerates the cyclic regeneration of active sites in the Fenton reaction and drives the activation of H2O2 (or PMS) to generate hydroxyl radicals (•OH) and sulfate radicals (SO4•). - (and other oxygen-containing active species)
[0035] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0036] Example 1: Phosphate-modified ultrathin graphitic carbon nitride nanosheets supporting cobalt hydroxide composite photo-Fenton catalyst (Co(OH)2@PCN)
[0037] (a) Bulk graphitic carbon nitride (UCN)
[0038] The preparation method is as follows:
[0039] Weigh 20 g of urea and place it in a covered corundum crucible. Then place the crucible in a muffle furnace and calcine at 550 °C at a heating rate of 3 °C / min under air atmosphere for 3 h. After natural cooling to room temperature, collect the resulting yellow solid product, which is bulk graphitic carbon nitride, denoted as UCN. Grind the product thoroughly into a fine powder using a mortar and pestle for later use.
[0040] (ii) Phosphate-modified ultrathin graphitic carbon nitride nanosheets (PCN)
[0041] The preparation method is as follows:
[0042] Weigh 10.0 g of urea and 1.0 g of urea phosphate and grind them thoroughly in a mortar until they are evenly mixed. Transfer the resulting powder mixture to a covered corundum crucible and place it in a muffle furnace. Calcinate the crucible in air at a heating rate of 3 °C / min to 550 °C and hold for 3 h. After naturally cooling to room temperature, collect the resulting pale yellow solid product, which is the phosphate-modified ultrathin graphitic carbon nitride nanosheet, denoted as PCN.
[0043] (III) Composite photo-Fenton catalyst (Co(OH)2@PCN)
[0044] The preparation method is as follows:
[0045] Co(NO3)2·6H2O (10 mg, 0.034 mmol) was dissolved in 50 mL of anhydrous ethanol to obtain a cobalt nitrate ethanol solution.
[0046] 100 mg of PCN material was added to a cobalt nitrate ethanol solution and stirred until evenly dispersed. Then, 8 mL of 0.025 mol / L NaOH solution was added dropwise, and the reaction was carried out under continuous stirring at room temperature for 5 h. After the reaction was completed, the product was washed three times each with deionized water and anhydrous ethanol, and then dried at 60 °C for 12 h to obtain a phosphate-modified ultrathin graphitic carbon nitride nanosheet-supported cobalt hydroxide composite photo-Fenton catalytic material, denoted as Co(OH)2@PCN.
[0047] (iv) Characterization
[0048] 1. Figure 1 XRD patterns representing the crystal structures of UCN, PCN, and Co(OH)₂@PCN prepared in this embodiment. Figure 1 It is evident that UCN possesses good crystallinity. Compared to UCN, the intensity of the (100) crystal plane diffraction peak at 13.0°, belonging to the carbon nitride interlayer stacking structure, in PCN is significantly reduced, indicating that phosphate modification weakens the periodic structure within the two-dimensional plane of the material. Compared to PCN, the crystal structure of Co(OH)₂@PCN does not show significant changes, suggesting that the loading of Co(OH)₂ nanoparticles does not significantly affect the intrinsic structure of the PCN support.
[0049] 2. Figure 2 SEM images of UCN (a), PCN (b), and Co(OH)2@PCN (c) prepared in this embodiment. Figure 2 As can be seen in (a), UCN consists of nanosheets with good crystallinity. Figure 2 As can be seen in (b), PCN exhibits an ultrathin porous nanosheet morphology. Figure 2As can be seen in (c), the microstructure of Co(OH)2@PCN did not change significantly compared to PCN, indicating that the loading of Co(OH)2 nanoparticles did not have a significant impact on the intrinsic structure of the PCN support.
[0050] 3. Figure 3 The UV-Vis diffuse reflectance spectra of UCN, PCN, and Co(OH)2@PCN prepared in this embodiment are shown. Figure 3 As can be seen, the light absorption edge of UCN is located at approximately 450 nm. Compared to UCN, PCN exhibits a significant blue shift in its light absorption edge, which can be attributed to the quantum size effect induced by the ultrathin porous structure resulting from phosphate modification. Compared to PCN, the light absorption properties of Co(OH)₂@PCN do not show significant changes, indicating that the loading of Co(OH)₂ nanoparticles does not significantly affect the intrinsic structure and properties of the PCN support.
[0051] 4. Figure 4 The instantaneous photocurrent diagrams of UCN, PCN, and Co(OH)2@PCN prepared in this embodiment are shown. Figure 4 As can be seen, the photocurrent density of PCN is significantly higher than that of UCN, indicating that the ultrathin porous structure effectively enhances the separation efficiency of photogenerated carriers. After loading Co(OH)2 nanoparticles, the photocurrent density of Co(OH)2@PCN is further improved compared with that of single-phase PCN, indicating that the construction of heterojunction further improves the separation efficiency of photogenerated carriers.
[0052] 5. Figure 5 TEM (a) and a magnified partial image (b) of the Co(OH)₂@PCN material prepared in this embodiment. Figure 5 It is evident that the Co(OH)2 nanoparticles are uniformly dispersed and loaded on the surface of the PCN sheets, indicating that phosphate modification effectively promotes the highly uniform loading of the active components.
[0053] Example 2: Phosphate-modified bulk graphitic carbon nitride supported cobalt hydroxide composite photo-Fenton catalyst (Co(OH)2@PMCN)
[0054] (a) Phosphate-modified bulk graphitic carbon nitride (PMCN)
[0055] The preparation method is as follows:
[0056] Weigh 10.0 g of melamine and 1.0 g of melamine phosphate and grind them thoroughly in a mortar until they are evenly mixed. Transfer the resulting powder mixture to a covered corundum crucible and place it in a muffle furnace. Calcinate the crucible in air at a heating rate of 3 °C / min to 550 °C and hold for 3 h. After naturally cooling to room temperature, collect the resulting pale yellow solid product, which is phosphate-modified bulk graphitic carbon nitride, denoted as PMCN.
[0057] (II) Composite photo-Fenton catalyst (Co(OH)2@PMCN)
[0058] The preparation method is as follows:
[0059] Co(NO3)2·6H2O (10 mg, 0.034 mmol) was dissolved in 50 mL of anhydrous ethanol to obtain a cobalt nitrate ethanol solution.
[0060] 100 mg of PMCN material was added to a cobalt nitrate ethanol solution and stirred until evenly dispersed. Then, 8 mL of 0.025 mol / L NaOH solution was added dropwise, and the reaction was carried out under continuous stirring at room temperature for 5 h. After the reaction was completed, the product was washed three times each with deionized water and anhydrous ethanol, and then dried at 60 °C for 12 h to obtain a phosphate-modified bulk graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalyst, denoted as Co(OH)2@PMCN.
[0061] (iii) Characterization
[0062] Figure 6 TEM images of the PMCN(a) and Co(OH)2@PMCN(b) materials prepared in this embodiment. Figure 6 As shown in Figure 6a, PMCN exhibits a morphology of micron-sized bulk stacks. Meanwhile, the loading of Co(OH)2 nanoparticles did not significantly affect the intrinsic structure of the PMCN support (Figure 6b).
[0063] Example 3: Application of phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalyst in photo-Fenton purification of antibiotics in water.
[0064] (I) The effect of different photo-Fenton catalysts on the photo-Fenton purification of antibiotics in water
[0065] 1. Comparative Example – Co(OH)2@UCN PhotoFenton Catalyst
[0066] The preparation method is as follows:
[0067] Co(NO3)2·6H2O (10 mg, 0.034 mmol) was dissolved in 50 mL of anhydrous ethanol to obtain a cobalt nitrate ethanol solution.
[0068] 100 mg of UCN material was added to a cobalt nitrate ethanol solution and stirred until evenly dispersed. Then, 8 mL of 0.025 mol / L NaOH solution was added dropwise, and the reaction was carried out under continuous stirring at room temperature for 5 h. After the reaction was completed, the product was washed three times each with deionized water and anhydrous ethanol, and then dried at 60 °C for 12 h to obtain a bulk graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalyst, denoted as Co(OH)2@UCN.
[0069] 2. Catalytic purification of water containing antibiotics using photo-Fenton technology
[0070] UCN, PCN, Co(OH)2@PCN prepared in Example 1, and Co(OH)2@UCN prepared in the comparative example were used as photo-Fenton catalysts for the visible light degradation of antibiotic pollutants. The methods are as follows:
[0071] Ciprofloxacin, an antibiotic pollutant found in representative water bodies, was used as the target pollutant. 10 mg of the aforementioned photo-Fenton catalyst was added to 50 mL of a 20 mg / L ciprofloxacin solution. After dark reaction adsorption equilibrium was reached, 0.3 g / L of PMS was added, and the reaction was carried out under a light intensity of 45 mW / cm². 2 Photo-Fenton catalytic degradation experiments were conducted under visible light. Samples were taken at fixed time intervals, filtered through a 0.45 μL filter, and the residual concentration of ciprofloxacin was analyzed by high-performance liquid chromatography. The results are as follows: Figure 7 .
[0072] from Figure 7 It can be seen that: 1) Under PMS alone or with only Co(OH)2@PCN catalyst, the degradation of ciprofloxacin concentration was approximately 9% and 58% after 30 min of light irradiation, respectively. This result indicates that the traditional PMS Fenton technique and photocatalysis have limited degradation effects on ciprofloxacin. 2) Without light, the addition of PMS significantly enhanced the degradation of ciprofloxacin by Co(OH)2@UCN and Co(OH)2@PCN; after 30 min of reaction, ciprofloxacin was degraded by 49% and 89%, respectively. This result indicates that the addition of carbon nitride support is beneficial to the traditional Fenton reaction, and phosphate modification further enhances the Fenton reaction. 3) Under both light and PMS conditions, Co(OH)2@PCN exhibited highly efficient photo-Fenton degradation performance of ciprofloxacin, with 20 mg / L of ciprofloxacin being completely degraded within 15 min. After reacting with light and PMS for 30 minutes, Co(OH)2@UCN can degrade about 80% of ciprofloxacin, while UCN and PCN can only achieve 19% and 38% degradation rates of ciprofloxacin, respectively.
[0073] (II) Effect of Co(OH)2@PCN prepared with different mass ratios of nitrogen-rich precursor and phosphorylated nitrogen-rich precursor on photo-Fenton purification of antibiotics in water
[0074] 1. Co(OH)2@PCN prepared by different mass ratios of nitrogen-rich precursors to phosphorylated nitrogen-rich precursors
[0075] The preparation method is as follows:
[0076] 10.0 g of urea and 0.1 g, 0.5 g, 1.0 g, and 2.0 g of urea phosphate were weighed and ground thoroughly in a mortar until homogeneous. The resulting powder mixture was transferred to a covered corundum crucible and then placed in a muffle furnace. Under air atmosphere, the temperature was increased to 550 °C at a heating rate of 3 °C / min and calcined for 3 h. After natural cooling to room temperature, the resulting pale yellow solid product was collected to obtain PCN with different mass ratios of nitrogen-rich precursor to phosphorylated nitrogen-rich precursor.
[0077] Co(NO3)2·6H2O (10 mg, 0.034 mmol) was dissolved in 50 mL of anhydrous ethanol to obtain a cobalt nitrate ethanol solution.
[0078] PCN materials (100 mg) with different mass ratios of nitrogen-rich precursor to phosphorylated nitrogen-rich precursor were added to a cobalt nitrate ethanol solution. After thorough dispersion, 8 mL of 0.025 mol / L NaOH solution was added dropwise, and the reaction was carried out under continuous stirring at room temperature for 5 h. After the reaction was completed, the product was washed three times each with deionized water and anhydrous ethanol, and then dried at 60 °C for 12 h to obtain Co(OH)2@PCN with different mass ratios of nitrogen-rich precursor to phosphorylated nitrogen-rich precursor.
[0079] 2. Catalytic purification of water containing antibiotics using photo-Fenton technology
[0080] 10 mg of Co(OH)₂@PCN at different mass ratios of nitrogen-rich precursor to phosphorylated nitrogen-rich precursor were added to 50 mL of 20 mg / L ciprofloxacin solution. After adsorption equilibrium was reached in the dark reaction, 0.3 g / L PMS was added, and the mixture was subjected to a light intensity of 45 mW / cm². 2 The sample was subjected to photo-Fenton catalytic degradation under visible light for 30 min. After filtering the sample through a 0.45 μL filter, the residual concentration of ciprofloxacin was analyzed by high-performance liquid chromatography (HPLC), and the degradation rate was calculated. The results are shown in Table 1.
[0081] Table 1
[0082]
[0083] As shown in Table 1, the degradation of ciprofloxacin first increases and then decreases with the increase of the mass ratio of urea to urea phosphate. When the ratio exceeds 10:1, the degradation rate decreases. Therefore, the present invention preferably uses a mass ratio of nitrogen-rich precursor: phosphorylated nitrogen-rich precursor = 10: (0.5 - 1).
[0084] (III) Effects of Co(OH)2@PCN and Co(OH)2@PMCN composites prepared with different precursors on photo-Fenton purification of antibiotics in water
[0085] 10 mg of Co(OH)₂@PCN and Co(OH)₂@PMCN prepared in Examples 1 and 2 respectively were added to 50 mL of ciprofloxacin solution with a concentration of 20 mg / L. After dark reaction adsorption equilibrium was reached, 0.3 g / L of PMS was added, and the solution was subjected to a light intensity of 45 mW / cm². 2 The sample was subjected to photo-Fenton catalytic degradation under visible light for 30 min. After filtering the sample through a 0.45 μL filter, the residual concentration of ciprofloxacin was analyzed by high-performance liquid chromatography (HPLC), and the degradation rate was calculated. The results are shown in Table 2.
[0086] Table 2
[0087]
[0088] As shown in Table 2, the Co(OH)₂@PCN catalyst with an ultrathin porous structure prepared using urea and urea phosphate as precursors exhibits significantly better performance than the bulk Co(OH)₂@PMCN composite catalyst prepared using melamine and melamine phosphate. Therefore, this invention preferably uses urea and urea phosphate as precursors to prepare the required catalyst materials.
[0089] (iv) Effects of Co(OH)2@PCN on photo-Fenton purification of water with different antibiotics
[0090] 10 mg of Co(OH)₂@PCN prepared in Example 1 was added to 50 mL of ofloxacin, norfloxacin, and tetracycline solutions with a concentration of 20 mg / L, respectively. After dark reaction adsorption equilibrium was reached, 0.3 g / L of PMS was added, and the mixture was subjected to a light intensity of 45 mW / cm². 2 Photo-Fenton catalytic degradation experiments were conducted under visible light. Samples were taken at fixed time intervals, filtered through a 0.45 μL filter, and the residual antibiotic concentration was analyzed by high-performance liquid chromatography (HPLC). Results are as follows: Figure 8 .
[0091] from Figure 8As can be seen, under the conditions of light and PMS, the Co(OH)2@PCN catalyst exhibits highly efficient and broad-spectrum photo-Fenton degradation performance of antibiotics; after a reaction time of 30 min, it can achieve a 100% degradation rate of tetracycline, an 88% degradation rate of ofloxacin, and an 80% degradation rate of norfloxacin.
[0092] The results of the embodiments show that the present invention, through the ultrathin porous structure design, effectively shortens the bulk migration distance of photogenerated carriers and achieves efficient separation of photogenerated electron-hole pairs. Surface phosphate modification not only achieves highly uniform loading of the Co(OH)2 active component but also promotes the migration and transport of photogenerated electrons to the surface active sites, accelerating the cyclic regeneration of Fenton reaction active sites. This catalytic material can be directly applied to the photo-Fenton purification of various antibiotic pollutants in water under simulated sunlight excitation, solving the technical problems of severe carrier recombination and low catalytic efficiency in traditional g-C3N4-based photocatalytic materials.
Claims
1. A phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material, characterized in that, The preparation method includes the following steps: (1) Mix the nitrogen-rich precursor and the phosphorylated nitrogen-rich precursor evenly, and calcine the resulting mixture in an air atmosphere to obtain phosphate-modified graphitic carbon nitride. (2) Add the phosphate-modified graphitic carbon nitride obtained in step (1) to the cobalt nitrate ethanol solution, stir evenly, and then add sodium hydroxide solution dropwise; stir at 10 ℃ - 60 ℃ for 1 h - 10 h, take it out, wash with deionized water and ethanol, and dry to obtain the phosphate-modified graphitic carbon nitride supported cobalt hydroxide composite photo-Fenton catalyst.
2. The phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material according to claim 1, characterized in that, The nitrogen-rich precursor is selected from one or a mixture of two or more of cyanamide, dinitrile diamine, urea, or melamine.
3. The phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material according to claim 1, characterized in that, The phosphorylated nitrogen-rich precursor is selected from one or a mixture of two or more of cyanamide phosphate, diamine dinitrile phosphate, urea phosphate, or melamine phosphate.
4. The phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material according to claim 1, characterized in that, In step (1), the mass ratio of nitrogen-rich precursor to phosphorylated nitrogen-rich precursor is 10: (0.1 - 2); preferably, the mass ratio of nitrogen-rich precursor to phosphorylated nitrogen-rich precursor is 10: (0.5 - 1).
5. The phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material according to claim 1, characterized in that, In step (1), the calcination conditions are: holding at 400 ℃ - 600 ℃ for 1 h - 6 h.
6. The phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material according to claim 1, characterized in that, In step (2), the mass ratio of phosphate-modified graphitic carbon nitride to cobalt nitrate is 100:(1-10).
7. The phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material according to claim 1, characterized in that: In step (2), the molar ratio is cobalt nitrate:sodium hydroxide = 1:(1-10).
8. The application of the phosphate-modified graphitic carbon nitride-supported cobalt hydroxide composite photo-Fenton catalytic material according to any one of claims 1-7 in the photo-Fenton purification of antibiotics in water.
9. The application according to claim 8, characterized in that, The method is as follows: Phosphate-modified graphite-phase carbon nitride-supported cobalt hydroxide composite photo-Fenton catalyst is added to water containing antibiotics. After the adsorption equilibrium is reached in the dark reaction, persulfate is added to the water, and photo-Fenton purification reaction is carried out under visible light.
10. The application according to claim 8 or 9, characterized in that, The antibiotics include ciprofloxacin, ofloxacin, norfloxacin, and tetracycline.
